Chemical Characteristics, Antioxidant Activity, Total Phenol, and Caffeine Contents in Coffee of Date Seeds (Phoenix dactylifera L.) of Red Sayer Variety - Siti Warnasih; Ade Heri Mulyati; Diana Widiastuti; Zuniar Subastian; Laksmi Ambarsari; Purwantiningsih Sugita (The Journal of Pure and Applied Chemistry Research, 2019)
Red Sayer is one of the date varieties from the United Arab Emirates. This variety is one type of dates that is imported into Indonesia and used as processed date palm juice producing waste, namely date seeds. Date seeds can be made into some coffee that is rich in antioxidants and does not contain caffeine. The purpose of this study is to determine the chemical characteristics, antioxidant activity, total phenol, and caffeine contents in coffee of the Red Sayer variety date seeds. Coffee of date seeds is made into powder and then analyzed for its contents of water, ash, protein, fat, carbohydrates and total sugar, besides its antioxidant activity, total phenol, and caffeine levels. The results of the analysis obtained are, as follows: 4.42±0.01% water, 1.17±0.04% ash, 8.55±0.64% protein, 7.34±0.07% fat, 78.52±0.76% carbohydrate, 16.39±0.01% total sugar, 23.81±0.22 μg/mL antioxidant activity (IC50) and 340.65±1.53 mg GAE / 100g total phenol, while caffeine is not detected. Red Sayer date seed coffee, therefore, can be a source of carbohydrates and natural antioxidants that does not contain caffeine.